Targeting in International Law Counterinsurgency and the Legal Materiality of the Principle of Distinction - Parsa, Amin (Interventions, 2024)
This book is about how distinctions are drawn between civilians and combatants in modern warfare and how the legal principle of distinction depends on the technical means through which combatants make themselves visibly distinguishable from civilians. The author demonstrates that technologies of visualisation have always been part of the operation of the principle of distinction, arguing that the military uniform sustained the legal categories of civilian and combatant and actively set the boundaries of permissible and prohibited targeting, and so legal and illegal killing. Drawing upon insights from the theory of legal materiality, visual studies, critical fashion studies, and a dozen of military manuals he shows that far from being passive objects of regulation, these technologies help to draw the boundaries of the legitimate target. With its attention to the co-productive relationship between law, technologies of visualisation and legitimation of violence, this book will be relevant to a large community of researchers in international law, international relations, critical military studies, contemporary counterinsurgency operations and the sociology of law.